2015
DOI: 10.1073/pnas.1518646112
|View full text |Cite
|
Sign up to set email alerts
|

The human gene damage index as a gene-level approach to prioritizing exome variants

Abstract: The protein-coding exome of a patient with a monogenic disease contains about 20,000 variants, only one or two of which are disease causing. We found that 58% of rare variants in the protein-coding exome of the general population are located in only 2% of the genes. Prompted by this observation, we aimed to develop a gene-level approach for predicting whether a given human protein-coding gene is likely to harbor disease-causing mutations. To this end, we derived the gene damage index (GDI): a genome-wide, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
247
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(256 citation statements)
references
References 63 publications
9
247
0
Order By: Relevance
“…While applying different genetic model filters with GEMINI, we also filtered variants to remove any where minimum heterozygous allelic balance was less than 0.25 or that had a "High" Gene Damage Index for general Mendelian diseases (http://lab.rockefeller.edu/casanova/GDI; ref. 50).…”
Section: Discussionmentioning
confidence: 99%
“…While applying different genetic model filters with GEMINI, we also filtered variants to remove any where minimum heterozygous allelic balance was less than 0.25 or that had a "High" Gene Damage Index for general Mendelian diseases (http://lab.rockefeller.edu/casanova/GDI; ref. 50).…”
Section: Discussionmentioning
confidence: 99%
“…P3 and P4, one boy and one girl, born to French and German parents, respectively, were aged 5 and 11 years when they developed VZV pneumonitis (P3) and encephalitis (P4 the predicted Mutation Significance Cutoffs (MSC) of 95% confidence (Supplemental Figure 3) (32,33). The genes themselves are highly conserved and subject to purifying selection, with low gene damage index and purification coefficient (34). Immunoblotting of peripheral blood mononuclear cell (PBMC) lysates from P1-P4 for levels of POLR3A and POLR3C revealed that these proteins were expressed at levels comparable to those in healthy controls ( Figure 1C).…”
Section: Identification Of Heterozygous Mutations In Polr3a and Polr3mentioning
confidence: 99%
“…For each group, 10,000 sets of 100 benign and 100 pathogenic variants were randomly sampled and tested from the full set of 25,765 variants and accuracy was calculated for gene-specific and genome-wide CADD and MAF thresholds Furthermore, calibration of pathogenic variants could be difficult in genes with high damage tolerance, i.e. having many missense or loss-of-function mutations [26]. In addition, calibration may be impaired by false input signals, such as an incorrect pathogenic classification in ClinVar or inclusion of disease cohorts in large databases such as ExAC could misrepresent allele frequencies [27].…”
Section: Discussionmentioning
confidence: 99%